Managing brand personality when brand undergoes sequential extension. (1st January 2011) - Pandey, Anuja
For managing the brand in the FMCG industry, the brand personality is a crucial variable and the company makes great efforts to communicate them to their target consumers. The wider the range of brands extended, the higher is the awareness the company needs regarding how their consumers perceive the extended brands. This research study shows the phenomenon of brand extension and examines the correlation of consumer perception on the parent brand and extended brand personalities as the brand undergoes sequential extension. The case study discusses the evolution and growth of brand in niche segment and its gradual extension into different product line. The key focus of the study is brand personality of Dove. The brand which was largely perceived as feminine brand has in year 2010 launched a new Dove Men + Care line. The case highlights the challenges thrown open due to this launch. Will this 360 degree stretch be an opportunity or an illusion?